INTERSUBJEKTIVITAS TREN CEWEK MAMBA DI INSTAGRAM - sekar sri wulan sari; Fatihatul Lailiyah; Ratnaningrum Zusyana Dewi (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2024)
This study discusses the phenomenon of the "cewek mamba" trend that emerged and spread through the Instagram social media platform. This trend associates women's fashion choices with the color black as an identity and a captivating style. Through in-depth interviews with informants, this research explores how women following the "cewek mamba" trend establish relationships and coexist with others through the Instagram social media platform. Informants choose the color black for its comfort, neutrality, and resulting elegant impression. The use of black color inspires others around them, creating a new identity recognized by many. The "cewek mamba" trend has an impact on self-perception and social interactions of the informants. They receive both positive and negative comments regarding their fashion style, but remain unaffected by the negative remarks and maintain confidence in their clothing choices. Wearing the "cewek mamba" outfit is done when engaging in activities outside the home and is shared on the Instagram social media platform to enhance self-existence and attract attention. Through these black garments, the informants acquire a distinctive feature that aids their recognition on social media platforms, especially on Instagram. The results of this research depict how fashion trends can influence social interactions and individual identities in the virtual realm.